An introduction to geotechnical design of South African wind turbine gravity foundations - Mawer, Byron Wade (Department of Civil Engineering, 2016)
With the increasing pressure on global governments to pursue more green and renewable energy production measures, wind based solutions have progressed into one of the most dominant development areas in the global renewable energy sector. In South Africa, with notable deficiencies in reliable energy supply, a number of wind projects have been planned in order to relieve the pressure on the nation's volatile reserves. With a lack of exposure to the complexities of wind turbine foundation design in Africa, this research aimed to present a methodology for the geotechnical design of gravity footings for these structures, specific to SA soil conditions and policies. To understand the implications of the main aim of the study, the current scope for renewable energy project uptake in South Africa was summarized, highlighting the scope and growth potential legislated by the Renewable Energy Independent Power Producer Procurement Programme. This summary indicates the current development corridors for wind projects that fall along the Eastern and South West coasts of the country and discusses the economics of wind farm ventures and their inherent ability to attract local and international investment. Additionally to this, topics including a basic introduction to turbine mechanics, tower and foundation types, and the effect of loading actions on the dynamic soil reactions, were presented. This was concluded by discussing gravity footings in context to other foundation types, and their advantages for use in these types of developments. With this understanding, the main research outcome was addressed by selecting three representative sites from each of the major wind development corridors, and using them as practical examples. These were resultantly named the Western Cape, Eastern Cape and Karoo sites. Soil profiles and properties were assumed based on site investigation data from real projects from each of these corridors and this data was compiled, discussed and used in the planning of three designs for each respective site. In this way, a geotechnical methodology was created addressing the critical criteria that require consideration for the construction of turbine base structures. These considerations included appropriate site investigation methods particularly suited for wind turbine foundations, such as Continuous Surface Wave testing, as well as bearing capacity calculations according to theories suggested by the DNV/Risφ (2002) guidelines and site-specific bearing capacity theories. Settlement concerns were addressed through the analysis of immediate elastic settlement beneath a foundation using a general elastic solution, a non-linear stepwise method as well as the computer software, Settle 3D. Unique to wind structures, the criterion of soil stiffness was considered in order address the structure's global resistance to rotation, caused by the high overturning moments inherent in these systems. The effect that the calculated finite soil stiffness has on the assumptions in computing the natural frequency of the system was also investigated. Finally, additional concerns such as the effect of gapping, issues with designing on pedogenic soils such as calcrete, as well as the use of the finite element method in the planning of turbine foundations, were discussed. In concluding the study, a general design process for engineers tasked with planning gravity footings for wind turbines subject to local soil conditions was presented.